Signal of opportunity based TDOA positioning using analog TV signals - Elgammal, Khaled Walid; Turan, Berke Can; Bedir, Oğuz; Çelebi, Hasari; Özdemir, Mehmet Kemal (IEEE Computer Society, 2023)
The ability to self-localize is an essential requirement for many systems. Mostly, this is accomplished by using a Global Positioning System (GPS) receiver. However, in some situations, the GPS receiver is disabled by external factors. Signal-Of-Opportunity (SoOP)-based localization is a popular substitute solution. TV broadcasting can be utilized for SoOP-based self-localization. In this paper, we collect measurements of Phase Alternating Modulation (PAL) analog TV broadcasting to aid the localization model. Specifically, we use these measurements to achieve a Time-Difference Of Arrival (TDOA) localization of one receiver with the knowledge of the coordinates of four transmitters and a reference receiver. The histogram of the localization error shows that the average error hits the theoretical limit of the employed bandwidth or the limit set by the time resolution of the samples.
Keywords: Analog TV; GPS; Localization; PAL; Signal-of-Opportunity; TDOA